Material Circularity on Modular Wall Panel Designs - Widyoputro, Muhammad Kholif Lir; Maghzaya, Abdul Robbi (Departement of Architecture, Universitas Islam Indonesia, 2025)
This study investigates the material circularity of modular wall panel designs using bamboo, wood, and light-gauge steel (LGS) as primary components. Through a comparative analysis of 9 representative panel prototypes, the research evaluates embodied energy (EE), recycling efficiency, and percentage of discarded material under a cradle-to-gate perspective to assess environmental performance. The study examines the relative circularity performance of bamboo, wood, and steel-framed panels. Furthermore, the research examined material configurations that best balance structural function and circularity. Key limitations include the modest sample size (9 prototypes), the educational provenance of prototypes (course-based fabrication), reliance on cradle-to-gate accounting rather than full life-cycle cost or in-service performance data, and uncertainty ranges in embodied-energy databases. Results indicate that biologically composed panels, such as bamboo and wood, demonstrate significantly lower EE and negligible discarded waste, aligning well with circular economy principles. These caveats are discussed and used to frame recommendations for further LCA, long-term performance testing, and scaled prototyping.